Branding Strategy Rumah Keramik Tanah Baru To Increase Tourists' Motivation To Visit - Shafa, Salsabila; Nugraha, Rizki Nurul (West Science Interdisciplinary Studies, 2024)
This research aims to analyze the branding strategies carried out by rumah keramik tanah baru and their implementation to increase tourist motivation to visit. Based on data from survey results via Instagram, the Tanah Baru Ceramic House still does not introduce its identity as a tourist attraction, namely educational tourism, culinary tourism, wedding event locations, and so on. Data was obtained through interviews with managers, employees, and visitors to Rumah Keramik, as well as through literature studies, journals, e-books, and official websites. Data analysis using Nvivo and SWOT analysis. The research results show that tourists are motivated because of the activities they can do, namely making ceramics. The ceramic house created a branding strategy to build brand awareness by creating a direct touch through the logo and tagline as the identity of the ceramic house. There is a driving factor to increase tourist motivation, namely implementing the "Fun With Clay" tour package promotion system. However, obstacles also influence the motivation to visit the rumah keramik, namely the health crisis, infrastructure and competitors